Anti-fatigue effect of ferulic acid in exercise trained mice - XIANCHU LIU; MING LIU (Polskie Towarzystwo Farmaceutyczne, 2023)
Ferulic acid (FA) was proved to have various pharmacological characteristics in muscle function. Fatigue is closely linked with muscle dysfunction. However, the correlation between fatigue and FA is unclear. Hence, our aim was to appraise anti-fatigue property of FA in exercise trained mice. Our results displayed FA enhanced exhaustion time and grip strength to postpone fatigue. In excessive exercise, FA reduced serum CK, LDH, ALT and AST levels to protect against liver and muscle damage. In liver and muscle, FA improved glycogen contents to increase substance of energy source. In skeletal muscle, FA restrained oxidative stress by accelerating SOD, CAT and GSH-PX activites, and mitigating MDA level. Moreover, FA also attenuated inflammatory response by decreasing TNF-a and IL-6 levels. Lastly, FA ameliorated energy metabolism by increasing Na+-K+-ATPase and SDH activities. In conclusion, FA protected against excessive exercise-fatigue through improvement of energy supply, oxidative stress, inflammatory response and energy metabolism-correlated enzymes.